Evaluation of sleep quality and daytime sleepiness in medical students: Its prevalence throughout the course (Research, Society and Development, 2023)
Sleep quality and daytime sleepiness are important factors for the physical, social, and emotional well-being of students. The Pittsburgh Sleep Quality Index assesses an individual's perception of their sleep quality, latency, and duration. Additionally, the Epworth Sleepiness Scale quantifies the degree of daytime sleepiness. Thus, this research aimed to, through the analysis of these two methods, establish a correlation between the evaluated criteria and the complexity with which their multiple influencing factors are interwoven. The results revealed a significant variation in sleep quality over the course periods, with some periods showing notably better or worse sleep quality compared to others. In conclusion, the findings of this study provide valuable insights into sleep quality and sleepiness among medical students. These discoveries can serve as a foundation for implementing student health support strategies aimed at improving sleep quality, and consequently, overall well-being and academic performance.